The one recipe recipe book, or, The artist's friend - Dunning, Christopher Lea (Carleton University Press, 1995)
So, who are you? A poet, musician, painter, sculptor, dancer, actor, a singer, or one of the many striving in the cultural sweatshop? Like most slaves to the Muse you are probably cash-poor, but you need a clear head and healthy body to be an artist. Well . you can do it on $15 a week. Here is The One Recipe Recipe Book : a thoroughly engaging, ecologically friendly and vegetarian affirmative approach to breakfast, lunch and dinner. Conceived and created with the starving artist (and student) in mind, this culinary jewel appeals not only to the palate and pocketbook, but to our appetite for the picturesque in life.